On the strong matrix Hamburger moment problem - Zagorodnyuk, S. M. (Ukrains’kyi Matematychnyi Zhurnal, 2010)
We obtain necessary and sufficient conditions for the solvability of the strong matrix Hamburger moment problem. We describe all solutions of the moment problem by using the fundamental results of A. V. Shtraus on generalized resolvents of symmetric operators.